(untitled) (African Journal of Biomedical Research, 2020)
Taraxacum officinaleis commonly known as ‘dandelion’. The aim of the study was to evaluate the effect of aqueous extract of Taraxacum officinale leaf on antioxidant status of the liver in streptozotocin (STZ)-induced diabetic male Wistar rats. The rats were divided into six groupsof6 rats each: Normal control, Diabetic control, Non-diabetic rats + 100 mg/kgbw extract, Non-diabetic rats + 200 mg/kgbw extract, Diabetic rats + 100 mg/kgbw extract and Diabetic rats + 200 mg/kgbw extract. After the treatment period, the animals were sacrificed and the liver was collected, homogenized for biochemical analyses. The Ferric reducing antioxidant power (FRAP), nitrite level, lipid peroxidation product (LPO), reduced glutathione (GSH) and activities of antioxidant enzymes (superoxide dismutase-SOD and glutathione peroxidase-GPx) were determined using established techniques. The levels of LPO and nitrite in the liver were decreased significantly (p < 0.05) in diabetic rats treated with 100 mg/kgbw and 200 mg/kgbw Taraxacum officinaleextracts as compared to the diabetic control. The liver showed no significant differences in FRAP level in treated diabetic rats compared to the diabetic control. The level of GSH as well as percentage SOD activity increased significantly in the diabetic rats treated with 100 mg/kgbw and 200 mg/kgbw Taraxacum officinale extractsas compared to the diabetic control while the level of GPx showed no significant difference across the groups. The results indicate that Taraxacum officinale could enhance liver anitioxidant status and hence, could be useful in the management of diabetic-induced liver injury due to prolong hyperglycemia